2020
DOI: 10.1186/s40168-020-00936-4
|View full text |Cite
|
Sign up to set email alerts
|

New viral biogeochemical roles revealed through metagenomic analysis of Lake Baikal

Abstract: Background Lake Baikal is the largest body of liquid freshwater on Earth. Previous studies have described the microbial composition of this habitat, but the viral communities from this ecosystem have not been characterized in detail. Results Here, we describe the viral diversity of this habitat across depth and seasonal gradients. We discovered 19,475 bona fide viral sequences, which are derived from viruses predicted to infect abundant and ecologically important taxa that reside in Lake Baikal, such as Nitro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 72 publications
2
41
0
Order By: Relevance
“…Viruses were also assigned to their putative hosts by comparing the shared genetic content between viruses and hosts described in Coutinho et al (2020). Bacterial and Archaeal genomes from the NCBI RefSeq database were used as reference genomes.…”
Section: Computational Host Prediction Of Viral Sequencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Viruses were also assigned to their putative hosts by comparing the shared genetic content between viruses and hosts described in Coutinho et al (2020). Bacterial and Archaeal genomes from the NCBI RefSeq database were used as reference genomes.…”
Section: Computational Host Prediction Of Viral Sequencesmentioning
confidence: 99%
“…GTDB was used to assign taxonomy to the reference genomes. CRISPR spacers (three points), homology matches (two points), and shared tRNAs (one point) were analyzed as virushost association signals as described in Coutinho et al (2020).…”
Section: Computational Host Prediction Of Viral Sequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the viral communities in shallow and deep-water regions, as well as in the southern and central basins, also significantly differ ( p -value < 0.05). A recent study [ 75 ] showed a vertical distribution and significant changes between epipelagic and bathypelagic Baikal viral community composition recovered from cellular metagenomes (fraction more than 0.22 μm). Accordingly, the difference between deep-water samples V1, V2, and V4 from other Baikal ones is partly explained by the presence of bathypelagic viral communities in them.…”
Section: Discussionmentioning
confidence: 99%
“…Viruses of prokaryotes are extraordinarily numerous in aquatic environments [ 1 , 2 ], commonly outnumbering cells by a factor of 5 to 10 [ 3 ]. They play significant roles in a variety of important biological and biogeochemical processes, including the lysis of cells and the consequent release of organic matter, selective sweeps of prokaryotic populations that drive the evolution of both virus and host, the acceleration of genetic exchange and the redirection of host metabolism [ 4 ]. They continue to provide a source of surprising new discoveries and insights, such as the BREX (BacteRiophage EXclusion) defense system [ 5 ] of bacteria and the viral counter defense to this based on the DNA mimic protein Ocr [ 6 ].…”
Section: Introductionmentioning
confidence: 99%